¡Viva la Causa! - Manuel Echavarria:::photographer::: (2025)
During this decade, hundreds would participate in the causa, thus making an historic up-surge in the Mexican and Chicano community's participation in the valley's public life. Durante esta década, cientos de personas participaron, incrimentando inesperadamente la participación de las comunidades mexicana y chicana en la vida pública del Valle de Santa Maria.